ADVERTISING AND MARKETING ETHICS OF SHARIA BANKING - Kartika Saraswati; Tirtha Shafa Serena; Tasya Uzmah Ibnah Fuad; Husnul Khatimah Sylvia (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2019)
This article was prepared with the aim of describing an advertising code of ethics that is in accordance with sharia and the relevance of marketing to sharia banking. This paper is divided into several sections, the first explains the concept of islamic business ethics, the second part discusses islamic ethics about marketing, and the last discussion is about how to implement business ethics values derived from Muhammad’s praiseworthy in advertising islamic banking products.